1998
DOI: 10.1046/j.1365-2958.1998.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Alginate, inorganic polyphosphate, GTP and ppGpp synthesis co‐regulated in Pseudomonas aeruginosa: implications for stationary phase survival and synthesis of RNA/DNA precursors

Abstract: SummaryThe regulatory protein AlgR2 in Pseudomonas aeruginosa positively regulates nucleoside diphosphate kinase (Ndk) and succinyl-CoA synthetase, enzymes critical in nucleoside triphosphate (NTP) formation. AlgR2 positively regulates the production of alginate, GTP, ppGpp and inorganic polyphosphate (poly P). An algR2 mutant with low levels of these metabolites has them restored by introducing and overexpressing either the algR2 or the ndk gene into the algR2 mutant. Thus, Ndk is involved in the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 30 publications
2
76
0
1
Order By: Relevance
“…Deletion of algQ leads to cell death at late exponential phase, a clear consequence of the inability of this mutant to adapt from exponential-phase cell growth to survival mode. This phenotype was rescued by overexpressing AlgQ or Ndk, confirming the role of these proteins in survival adaptation (107).…”
Section: Ppgpp and Pppgppsupporting
confidence: 54%
“…Deletion of algQ leads to cell death at late exponential phase, a clear consequence of the inability of this mutant to adapt from exponential-phase cell growth to survival mode. This phenotype was rescued by overexpressing AlgQ or Ndk, confirming the role of these proteins in survival adaptation (107).…”
Section: Ppgpp and Pppgppsupporting
confidence: 54%
“…480 aa) with both PMI and GDP-mannose pyrophosphorylase (GMP) (EC 2.7.7.22) activity. An example of the latter type of protein, and one of particular practical importance, is the 56-kDa bifunctional enzyme encoded by algA (179,196,259), which catalyzes the first and third steps in the biosynthesis of alginate, PMI catalyzing the first step (152). This compound is composed of 1,4-linked ␣-Lguluronic acid and ␤-D-mannuronic acid and is of great economic importance, although for commercial production it is usually extracted from marine seaweeds rather than from bacteria (237).…”
Section: Phosphomannose Isomerasesmentioning
confidence: 99%
“…We previously reported that Ndk, which is normally responsible for all NTP formation in the cell, is important for alginate synthesis (24), since it forms complexes with a number of cellular proteins in P. aeruginosa and since such complexes generate predominantly GTP (4,5). It should be noted, however, that GTPgenerating complexes of Ndk with proteins such as pyruvate kinase or Pra (4,5,24) involves the truncated 12-kDa form of Ndk, which is generated uniquely in the mucoid cells by the periplasmic retention of elastase (9,12). An ndk knockout mutant (27), while deficient in alginate synthesis, nevertheless, makes small amounts of alginate.…”
Section: Discussionmentioning
confidence: 99%
“…The Scs protein was shown to copurify with Ndk in P. aeruginosa (10). Ndk exists in two forms in mucoid P. aeruginosa, a cytoplasmic 16-kDa form capable of generating all of the NTPs and a 12-kDa membrane-associated form which forms complexes with pyruvate kinase, Pra, or EF-Tu, and these complexes predominantly use GDP as a substrate, generating GTP (5,12,18). Since Scs copurifies with Ndk, it was of interest to see if Scs modulates Ndk activity in any way.…”
Section: Ndp Kinase Activities Of the Scs With [␥-32 P]atp Or [␥-mentioning
confidence: 99%